RELATIONSHIP BETWEEN ANTHROPOMETRIC INDICATORS AND CORONARY OSTIA DIMENSIONS IN MEN - Pidvalna, U.Ye.; Mateshuk-Vatseba, L.R.; Beshley, D.M.; Harapko, T.V.; Hresko, N.I. (World of Medicine and Biology, 2022)
The size of the coronary arteries is an essential parameter in assessing coronary anatomy, which depends on age and anthropometric indicators. However, there is limited data on the correlation between biometric indicators and coronary arteries’ size among Ukrainian residents. The purpose of the study is to evaluate the size of the coronary ostia and study their correlation with age, height, weight, body mass index, and body surface area in men with and without coronary artery disease using coronary angiography. The study group consisted of 98 patients: 64 patients with and 34 patients without lesions of the coronary arteries (treated as healthy or within the norm). In patients with no coronary artery disease, the ostium of the left coronary artery is higher than that of the right coronary artery: 5.94±1.41 mm versus 5.09±1.36 mm, p=0.013. In men with coronary artery disease, the average parameters of the height of the left coronary artery (5.45±1.10 mm) are significantly more extensive than the height of the right coronary artery 4.91±1.05 mm (p=0.005). In the healthy group, a direct relationship of medium strength between the data of the height of the right coronary artery ostium and height was proven (r=+0.34, p=0.049), as well as an inverse relationship of medium strength between the value of the height of the right coronary artery ostium and age (r= -0.35, p=0.041). No correlation of age-anthropometric parameters with the value of the height of the ostium of the left coronary artery has been found. Relationships between the left coronary artery index and age, weight, and height have been established in men with coronary artery disease.